Educação escolar quilombola na comunidade jatobá: práticas pedagógicas e fazeres quilombolas - Oliveira, Élida Joyce de (Universidade Federal Rural do Semi-Árido, 2019)
This work has as proposal to analyze how Quilombola School Education has been developed as a teaching modality in the Lauro Maia Rural Education Unit, located in the quilombola community of Jatobá, in the city of Patu / RN. We tried to analyze the pedagogical practices of the Lauro Maia Rural Education Unit, in addition to contextualize historically the community, highlighting their daily experiences. The theoretical introduction of this study brought the concept of quilombo and the presentation of the National Curriculum Guidelines for Quilombola School Education, from which we made an approach about curriculum and the importance of working diversity and its meanings in the school environment. We present perceived elements in the research process with the Jatobá community, addressing the specificities of the remaining Jatobá quilombolas. We tried to understand daily life through observations and informal conversations with people in the community. We then discuss the relationship between school, family and community. Thus, we highlight how the pedagogical practices are developed by teachers of the quilombola community and if they are in accordance with the recommendations of the National Curriculum Guidelines for Quilombola School Education. The methods for carrying out this work range from bibliographic research to field research. Thus, the result shows that Quilombola School Education faces many challenges to be implanted on the school floor. In the case of UERLM, the pedagogical actions are not aligned with those of the quilombola community of Jatobá, since the this school has not followed what is established by the National Curriculum Guidelines for Quilombola School Education. We realize that there is no integration between school, family and community, they do not participate in the Political Pedagogical Project which has hindered the construction of positive identities
Keywords: Escola; Ensino; Educação Quilombola; Quilombo; School; Teaching; Quilombola Education; Quilombo; MULTIDISCIPLINAR::ENSINO